Chiara Lubich's Pedagogy in the "Spiritual Thoughts of Collegamento CH" - Maria José Dantas (Nicolaus Copernicus University in Toruń, 2019)
The current study addresses the writings by Chiara Lubich, who founded the Focolare Movement in the 1940s. Lubich adopted the "Spiritual Thoughts" as an education resource capable of reaching people and places that she could not physically reach. In addition, throughout her life, she developed an educational approach seen as a different Catholic pedagogy perspective due to its notoriety in the religious and social spheres. The aim of the current study is to investigate, through the analysis of one of the "Spiritual Thoughts" by Chiara Lubich, how she configured her educational practice through messages and, more specifically, to assess the pedagogical approach in her writings. The reflection presents the concepts of charisma, religious field and symbolic relations based on the historical and social perspective as theoretical reference.